2022
DOI: 10.3389/fneur.2022.971664
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of pipeline embolization devices with shield technology for treating intracranial aneurysms

Abstract: IntroductionAs a common endovascular treatment for intracranial aneurysms, the pipeline embolization device (PED) is considered a standard treatment option, especially for large, giant, wide-necked, or dissecting aneurysms. A layer of phosphorylcholine biocompatible polymer added to the surface of the PED can substantially improve this technology. This PED with shield technology (pipeline shield) is relatively novel; its early technical success and safety have been reported. We conducted a systematic literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…These findings were consistent with the rates of complications reported in other large PED series, such as the PFLEX study, 12 PREMIER, 21 or IntrePED, 22 and Chinese cohorts, 23 validating the noninferiority and safety of the Shield technology. 24-26 However, it should be noted that some of the ischemic events are silent, and a prospective routine imaging analysis using diffusion-weight imaging (DWI) has indicated that ischemic lesions may occur in up to 16.6% of procedures, 27 potentially even higher in some analyses. 28,29 Nonetheless, other case series have shown DWI changes in patients after cerebral angiography posing limitations when attributing those changes solely to the FD.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were consistent with the rates of complications reported in other large PED series, such as the PFLEX study, 12 PREMIER, 21 or IntrePED, 22 and Chinese cohorts, 23 validating the noninferiority and safety of the Shield technology. 24-26 However, it should be noted that some of the ischemic events are silent, and a prospective routine imaging analysis using diffusion-weight imaging (DWI) has indicated that ischemic lesions may occur in up to 16.6% of procedures, 27 potentially even higher in some analyses. 28,29 Nonetheless, other case series have shown DWI changes in patients after cerebral angiography posing limitations when attributing those changes solely to the FD.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the requirements for DAPT, a new FDS with a hydrophilic polymer coating (p48-MW-HPC) has been developed. This has a similar goal to the novel PED-Shield: a FDS with a phosphorylcholine coating designed to reduce thrombogenicity [ 67 ]. Either of these devices may be preferred in cases of ruptured aneurysms due to the reduced need for antiplatelet agents [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has a similar goal to the novel PED-Shield: a FDS with a phosphorylcholine coating designed to reduce thrombogenicity [ 67 ]. Either of these devices may be preferred in cases of ruptured aneurysms due to the reduced need for antiplatelet agents [ 67 ]. Lobsien et al demonstrated the effectiveness of the p48-MW-HPC FDS under SAPT across 13 ruptured aneurysms and reported a single thromboembolic complication [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Pipeline with Shield Technology helps to reduce the use of antiplatelet drugs in patients who have nasal bleeds. 36 , 37 …”
Section: Discussionmentioning
confidence: 99%